Prinsip-prinsip Pengembangan Permukiman Produktif Terkait Industri Rumah Tangga - Nurul Inayah; Shirly Wunas; Mimi Arifin (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2018)
Pambusuang Village is a village that has home industry activities, namely mandar weaving gloves (lipaq saqbe), sandeq boat industry, and salted fish industry. Households in Pambusuang Village, analyzed the support of productive supporting facilities and infrastructure related to households in Pambusuang Village, and formulated the principles of productive settlements related to home industries in Pambusuang Village. Data collection methods used were observation, questionnaires, interviews, documentation and literature studies. The Meotode analysis used was qualitative descriptive analysis of comparative analysis, and spatial analysis. The results of this study indicate that each industry has an area of ​​60-150 m2 including the type of simple house. The pattern of house grouping according to each type of industrial activity is the distribution pattern and grouping pattern. Related facilities and infrastructure that support housing including transportation for raw material distribution and production, utilization of home industries, and so on. Based on residential product principles related to home industry: 1) feasibility of housing; (2) waste treatment system; (3) facilities and infrastructure that are easy to obtain home industry support; and (4) home industry social community.